Wychowanie fizyczne w Związku Harcerstwa Polskiego w latach międzywojennych realizowane poprzez obozy letnie = Physical education in Polish scouting association in the interwar years implemented during summer camps - Biczysko, Grażyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the interwar years, camping was one of the numerous ways of scouting activities that promoted physical education. Scout camps developed mainly during summer time and were indispensable means of physical education. They provided an opportunity to practice variety of sports in natural conditions.
Keywords: scouting; Związek Harcerstwa Polskiego; physical activity; interwar period; Poland; skauting; aktywność fizyczna; Polska; 1918-1939